Beginning jQuery - Franklin, Jack.; SpringerLink (Online service) (Berkeley, CA : Apress : Imprint: Apress, 2013)
Beginning jQuery is your step-by-step guide to learning the jQuery library. jQuery is the most popular JavaScript library in the web developer$1 (Bs toolkit. Jack Franklin takes you from the basics of getting you started with jQuery, right through to extending jQuery by writing your own plug-ins. You'll discover best practices you can follow, how you can avoid common mistakes, and you'll learn about so many of the things that jQuery has to offer, including how you can: Use jQuery$1 (Bs powerful tools to dynamically update content on your site, including DOM manipulation. Extend jQuery$1 (Bs capabilities by writing your own plugins on top of the framework. Animate elements and build your own jQuery slider. Employ best practices and avoid common errors made by beginners. JavaScript is a powerful language but every web developer must navigate the tricky issues around cross-browser inconsistencies. Beginning jQuery teaches you how to use jQuery to avoid spending your time fixing these browser bugs - letting you concentrate on what really matters to you. Throughout Beginning jQuery, you'll discover how expressive yet concise jQuery$1 (Bs code is and how much quicker and efficient you can develop with jQuery!s
Keywords: Computer science; Computer Science; Computer Science, general